Prevalence of overweight, obesity, and associated factors among healthcare workers in the Gaza Strip, Palestine: A cross-sectional study - Younis, Joma; Jiang, Hong; Fan, Yahui; Wang, Lina; Li, Zhaofang; Jebril, Majed; Ma, Mei; Ma, Le; Ma, Mao; Hui, Zhaozhao (Frontiers in Public Health, 2023)
Background: Overweight and obesity are multifactorial conditions that spread quickly in developing and developed countries. There are emerging as a significant public health concern among healthcare workers. We aimed to estimate the prevalence of overweight and obesity and their associated factors among HCWs in the Gaza Strip. Methods: A cross-sectional study was conducted to recruit 1850 HCWs aged 22 years and older. Interviews were carried out to collect sociodemographic information, nutritional information, and physical activity. Anthropometric measurements [height, weight, and waist circumference] were conducted with the HCWs. The body mass index was computed to determine the prevalence of overweight and obesity. Chi-square, t-test, and one-way ANOVA were used to compare the variables, Logistic regression was used to examine the associated factors of overweight and obesity. Results: The combined prevalence of overweight and obesity among HCWs was 65%. The result of logistic regression showed the risk of being overweight or obese increased within the age group (40-49) years (OR=3.20; 95% CI:2.37-4.32; P<0.001). Male participants were more likely to be obese than female participants (OR = 1.77; 95% CI: 1.45-2.15). Married participants had a significantly higher risk of being overweight and obese (OR=2.52; 95% CI:2.05-3.28; P=0.001). Increased monthly income was significantly associated with the risk of being overweight and obese (OR=2.16; 95% CI: 1.22-3.83; P=0.008). Furthermore, hypertension (OR = 2.49; 95% CI: 1.65-3.78; P 0.001) and type 2 diabetes (OR = 2.42; 95% CI: 1.21-4.85; P = 0.012) were linked to being overweight or obese. Finally, a family history of NCDs was associated with overweight and obesity (OR = 1.69; 95% CI: 1.38-2.07; P<0.001). Conclusions: This study showed a higher prevalence of overweight and obesity among HCWs than in previous studies. Age, monthly income, marital status, known HTN, type 2 diabetes, and eating habits were associated with the prevalence of overweight and obesity, compared to other variables that were not associated with overweight and obesity, such as profession, vegetable and fruit consumption, and physical activity. Urgent action is needed to tackle overweight and obesity among HCWs.